Instruction to start the work at BRACU new campus project (Sanitary wares fixtures and fittings) - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the instruction to start the work of supplying sanitary wares, fixtures and fittings for BRACU new campus project.